2015
DOI: 10.1097/01.aoa.0000472734.42973.28
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Timing of Death in Extremely Premature Infants From 2000 Through 2011

Abstract: BACKGROUND-Understanding the causes and timing of death in extremely premature infants may guide research efforts and inform the counseling of families. METHODS-We analyzed prospectively collected data on 6075 deaths among 22,248 live births, with gestational ages of 22 0/7 to 28 6/7 weeks, among infants born in study hospitals within the National Institute of Child Health and Human Development Neonatal Research Network. We compared overall and cause-specific in-hospital mortality across three periods from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
4
20

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(150 citation statements)
references
References 11 publications
6
120
4
20
Order By: Relevance
“…Much of the research that has been conducted relative to the preterm infant intestinal microbiome has reported on case‐control studies describing differences in the community structure of the microbiome under conditions of a disease state during the neonatal period. Inflammatory bowel disease, specifically necrotizing enterocolitis (NEC), disproportionally contributes to neonatal morbidity and mortality (Neu and Walker, ; Patel et al, ). NEC has been the focus of multiple case‐control studies (Wang et al, ; Mai et al, ; Claud et al, ; Morrow et al, ; Torrazza et al, ), because early intestinal colonization with pathogenic bacteria has long been thought to contribute to the pathogenesis of NEC (Neu and Walker, ).…”
Section: Part IImentioning
confidence: 99%
“…Much of the research that has been conducted relative to the preterm infant intestinal microbiome has reported on case‐control studies describing differences in the community structure of the microbiome under conditions of a disease state during the neonatal period. Inflammatory bowel disease, specifically necrotizing enterocolitis (NEC), disproportionally contributes to neonatal morbidity and mortality (Neu and Walker, ; Patel et al, ). NEC has been the focus of multiple case‐control studies (Wang et al, ; Mai et al, ; Claud et al, ; Morrow et al, ; Torrazza et al, ), because early intestinal colonization with pathogenic bacteria has long been thought to contribute to the pathogenesis of NEC (Neu and Walker, ).…”
Section: Part IImentioning
confidence: 99%
“…Preterm birth (PTB) is a major cause of perinatal morbidity and mortality. Worldwide, about 15 million babies are born too early every year, resulting in 1.1 million deaths as well as short‐ and long‐term disabilities in countless numbers of survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm babies are now surviving in greater numbers and for longer. For example, a review of 22 248 live births between 22 + 0 and 28 + 6 weeks of gestation in the United States between 2000 and 2011 showed that the number of deaths per 1000 live births fell from 275 between 2000 and 2003 to 258 between 2008 and 2011 and that only 17.3% of infants died after 28 days of age .…”
Section: Introductionmentioning
confidence: 99%